analisis blibiometrik terhadap berpikir kreatif matematika siswa: berpikir kreatif matematika - Nur Azira (PT PUSTAKA CENDEKIA GROUP, 2024)
In studying mathematics, everyone must be able to think well in order to cultivate high-level reasoning abilities which are the targets of learning mathematics. Reflective thinking ability is one of the classifications of higher order thinking skills that must be mastered properly. Through this research the aim is to be able to know the classification of mathematical reflective thinking skills with bibliometric analysis. This study utilizes Harzing's Publish or Perish (POP) software with Google Scholar sources with the keywords